Analysis of free sugar and starch in oil palm trunks (elaeis guineensis jacq.) from various cultivars as a feedstock for bioethanol production - Zubaidah Aimi Abdul Hamid; Takamitsu Arai; Mhd Ramlee Sitti Fatimah; Akihiko Kosugi; Othman Sulaiman; Rokiah Hashim; Satoru Nirasawa; Tanaka Ryokei; Bhadravati Eswara Lokesh; Kumar Sudesh; Yoshinori Murata; Masayoshi Saito; et al. (2015)
In this study, oil palm trunks from various plantations in Malaysia were analyzed for their starch content and sugar concentrations in the sap from the trunks as function of storage time as a feedstock for green energy. Glycoside hydrolases of the samples were also measured during storage. Considering three kinds of sugars accumulation in the trunks, the highest increase was from 31 mg/ml to 198 mg/ml after 60 days of storage followed by the second highest from 48~78 mg/ml to 109~133 mg/ml after 15~45 days of storage. Accumulation of the third stages was not observed in most types of trunks. The parenchyma in each trunk had different starch contents, which ranged from 0.33 to 37 wt%. Trunks with higher starch content in the parenchyma cells showed a tendency towards increased sugar concentration in the sap, suggesting that the breakdown of starch within the sap is related to sugar accumulation. Amylase activity in the trunks increased from 0.21 mU/g to 1.54 mU/g during storage. Invertase showed relatively high activity (6.48 mU/g) at around 15 days storage time. Based on the findings in this work, it seems that enzymes played an important role in the breakdown of starch and sucrose during storage of oil palm trunks.